Fluid Inclusions and C, H, O, S, and Pb Isotopic Compositions of the Dabaoshan Cu Polymetallic Deposit, Northern Guangdong Province, South China. Issue 3 (25th March 2018) - Qu, Hongying; Mao, Jingwen; Zhou, Shumin
Abstract: The Dabaoshan deposit in Northern Guangdong Province, South China, is a Cu–Mo–W–Pb–Zn polymetallic deposit, located in the southern part of the Qin–Hang porphyry–skarn Cu–Mo ore belt. The deposit mainly comprises porphyry Mo and stratiform skarn Cu ore deposits. The genesis of the Cu ore deposit has been ascribed to a typical skarn ore deposit formed by the metasomatism of Devonian carbonate rock layers or to a volcanic rock‐hosted massive sulfide deposit formed by marine exhalation. In this paper, we report on the homogenization temperatures and salinities of fluid inclusions and C, H, O, S, and Pb isotopic compositions of fluids and minerals in this deposit. Homogenization temperatures and salinities of fluid inclusions in garnet, diopside, quartz, and calcite provide information on the skarnification, mineralization, and postmineralization stages. The data show that ore‐forming fluids experienced a continuous transition from high temperatures and salinities to low temperatures and salinities over the entire period of mineralization. C, H, and O isotopic compositions indicate that ore‐forming fluids were derived mainly from magmatic water. O isotopic compositions indicate that ore‐forming fluids mingled with atmospheric water during the last stage of mineralization. Sulfur in the ore came mainly from deep magmatic sources. Pb isotopic compositions in the orebody show that almost all the lead in the ore was derived from magma with a crustal source. Combined geological, geophysical, and geochemical data were achieved before we proposed that the Dabaoshan porphyry–skarn Cu–Mo–W–Pb–Zn deposit, as one member of the Qin–Hang porphyry–skarn Cu–Mo ore belt, formed during the Jurassic subduction of the paleo‐Pacific plate beneath the Eurasian continent at quite low angle. NE‐ and EW‐trending structures controlled the emplacement of magmatic rocks in the South China region. In the mining area, the Xiangguanping Fault and its branches were the main conduits for magmatic crystallization and mineralization. The many subfaults, folds, and interlayer fracture zones on both sides of the main fault provided the requisite space for the ore and, together, were the controlling structures of the orebody. Abstract : Ore‐forming fluids represent a continuous process from high temperatures and salinities to low temperatures and salinities corresponding to the progressive development of mineralization. C, H, O, S, and Pb isotopic compositions show that ore‐forming fluids were derived mainly from magmatic water and ore‐forming materials came mainly from deep magmatic sources. Mineralization of the Dabaoshan deposit was associated with granodiorite porphyry of the Early Yanshanian, hydrothermal fluids of the post magma brought into ore‐forming materials and maybe extracted few metal materials.